Confession, word, and power: the miserable womanly existence (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Among the medieval German abbess Hildegard von Bingen (XII Century) and the Chilean late seventeenth century Clarisse Sister Ursula Suárez there exists a great historical and cultural distance. However, something strongly approximates them as if they were sisters of the same cloister. And this approach is not the clothing habits or the proclamation of vows of poverty, obedience and chastity, but it is, above all, the adventures that both had to live through in order to describe their spiritual experiences: ask permission of a male figure in the case of Hildegard, and submit to the obedience of this same figure in the case of Ursula. In this paper we propose to show how the discourses of the nuns who have written are subordinated to the approval of a model of power and authority.
Keywords: Hildegard von Bingen; Úrsula Suárez; Speech; Convent; Power